2022
DOI: 10.1071/wr22056
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the success of hand-reared juvenile brushtail possums (

Abstract: Context. Wildlife is ubiquitous in urban environments, resulting in frequent interactions with humans and human infrastructure. The result of these interactions is often negative, in the form of road injury, orphaning of dependent young or eviction from natural home ranges. Wildlife rehabilitation programmes are devised to counter these negative interactions. However, the success of current management strategies is rarely assessed. Aims. We aimed to determine whether short-term survival of juvenile hand-reared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Few studies have monitored post-release survival of rehabilitated wildlife, and even fewer have included an experimental design or control group [28]. A study of hand-raised brushtail possums found that 45% of releases were unsuccessful in the first four weeks [86], yet, from a long-term rehabilitation dataset, we know that rehabilitated koalas are capable of surviving in the wild long-term [87]. A study of koalas rehabilitated following fire found that the annual post-release survival rate was 58% compared with 67% for uninjured koalas, and predation by dogs was the leading cause of mortality in both cohorts [88].…”
Section: Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have monitored post-release survival of rehabilitated wildlife, and even fewer have included an experimental design or control group [28]. A study of hand-raised brushtail possums found that 45% of releases were unsuccessful in the first four weeks [86], yet, from a long-term rehabilitation dataset, we know that rehabilitated koalas are capable of surviving in the wild long-term [87]. A study of koalas rehabilitated following fire found that the annual post-release survival rate was 58% compared with 67% for uninjured koalas, and predation by dogs was the leading cause of mortality in both cohorts [88].…”
Section: Management Implicationsmentioning
confidence: 99%
“…The availability of suitable release locations within a short timeframe can be a challenge, particularly as unburnt habitats are likely to be refuges for fire survivors and already be at capacity. Research on the suitability and feasibility of translocation of rehabilitated wildlife is needed in situations where suitable release locations are limited [28], as keeping animals in care for longer periods will likely increase levels of humanisation, which has been linked with poor post-release outcomes [86].…”
Section: Management Implicationsmentioning
confidence: 99%
“…Koala admittance to wildlife hospitals had already been increasing over time 9 , 52 , and following the bushfires increased further 10 , 21 . Despite theoretical evidence that rehabilitated animals may contribute to population growth 3 , there is limited empirical data on post-release outcomes for rehabilitated koalas or similar species (e.g., brushtail possums 59 ) to guide investment and decision making in population management.…”
Section: Introductionmentioning
confidence: 99%
“…Koala admittance to wildlife hospitals had already been increasing over time 9,52 , and following the bush res increased further 10,21 . Despite an increased need, there is limited data on post-release outcomes for rehabilitated koalas or similar species (e.g., brushtail possums 57 ) to guide investment and decision making in population management.…”
Section: Introductionmentioning
confidence: 99%